Importance of Aggregated Islet Amyloid Polypeptide for the Progressive Beta-Cell Failure in Type 2 Diabetes and in Transplanted Human Islets. (22nd March 2009) - Westermark, Gunilla T.; Westermark, Per
Abstract :